Adeno‐Associated Virus 8 and 9 Myofibre Type/Size Tropism Profiling Reveals Therapeutic Effect of Microdystrophin in Canines - Matthew J. Burke; Braiden M. Blatt; James A. Teixeira; Dennis O. Pérez‐López; Yongping Yue; Xiufang Pan; Chady H. Hakim; Gang Yao; Roland W. Herzog; Dongsheng Duan (Journal of Cachexia, Sarcopenia and Muscle)
ABSTRACT Background Adeno‐associated virus (AAV) 8 and 9 are in clinical trials for treating neuromuscular diseases such as Duchenne muscular dystrophy (DMD). Muscle consists of myofibres of different types and sizes. However, little is known about the fibre type and fibre size tropism of AAV in large mammals. Methods We evaluated fibre type‐ and size‐specific transduction properties of AAV8 and AAV9 in 17 dogs that received systemic gene transfer (dose 1.94 ± 0.52 × 1014 vg/kg; injected at 2.86 ± 0.30 months; harvested at 20.79 ± 3.30 months). For AAV8, two DMD dogs and three carrier dogs received an alkaline phosphatase (AP) reporter vector, and five DMD dogs received a four‐repeat microdystrophin (uDys) vector. For AAV9, one normal and one DMD dog received the AP vector, and five DMD dogs received a five‐repeat uDys vector. Association between AAV transduction and the fibre type/size was studied in three muscles that showed mosaic transgene expression, including the biceps femoris, teres major and latissimus dorsi. Results Transgene expression was detected in 30%–45% of myofibres. In the AP reporter vector–injected dogs, neither AAV8 nor AAV9 showed a statistically significant fibre type preference. Interestingly, AP expression was enriched in smaller fibres. In uDys‐treated DMD dogs, slow and fast myofibres were equally transduced. Notably, uDys‐expressing myofibres were significantly larger than uDys‐negative myofibres irrespective of the AAV serotype (p < 0.0001). In AAV8 uDys vector–injected dogs, the mini‐Feret diameter was 15%, 16% and 23% larger in uDys‐positive slow, fast and hybrid fibres, respectively; the cross‐sectional area was 30%, 34% and 46% larger in uDys‐positive slow, fast and hybrid fibres, respectively. In AAV9 uDys vector–injected dogs, the mini‐Feret diameter was 12%, 13% and 25% larger in uDys‐positive slow, fast and hybrid fibres, respectively; the cross‐sectional area was 25%, 28% and 59% larger in uDys‐positive slow, fast and hybrid fibres, respectively. Conclusions Our studies suggest that AAV8 and AAV9 transduce fast and slow myofibres at equivalent efficiency. Importantly, uDys therapy effectively prevented dystrophic myofibre atrophy. Our study provides important insight into systemic muscle AAV delivery in large mammals and supports further development of uDys gene therapy for DMD.